2021
DOI: 10.2147/jir.s322724
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin Protects Against Airway Remodeling Through the Modulation of Autophagy via HMGB1 Suppression in House Dust Mite-Induced Chronic Asthma

Abstract: Purpose Airway remodeling is an important feature of chronic asthma, and yet there are few effective therapeutic strategies. Progranulin (PGRN) has been shown to have lung protective functions, but the role of PGRN in asthmatic airway remodeling is unclear. We aim to explore the protective potential of PGRN on house dust mite (HDM)-induced airway remodeling and the underlying mechanisms. Methods In this study, a murine model of chronic asthma was established by HDM sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Additionally, we found that NCOA4 knockdown alleviated HDM‐induced free iron level increases and reduced the cell death rate (Figure 7E,F). A recent study demonstrated that HDM activated autophagy in airway epithelial cells 30 . In agreement with this observation, HDM exposure increased the expression of the autophagy‐related protein LC3 in HBE cells (Figure 7G).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Additionally, we found that NCOA4 knockdown alleviated HDM‐induced free iron level increases and reduced the cell death rate (Figure 7E,F). A recent study demonstrated that HDM activated autophagy in airway epithelial cells 30 . In agreement with this observation, HDM exposure increased the expression of the autophagy‐related protein LC3 in HBE cells (Figure 7G).…”
Section: Resultssupporting
confidence: 86%
“…A recent study demonstrated that HDM activated autophagy in airway epithelial cells. 30 In agreement with this observation, HDM exposure increased the expression of the autophagy-related protein LC3 in HBE cells (Figure 7G). FTH accumulation was also enhanced when autophagy was inhibited by ATG5 and P62 siRNA transfection and by treatment with the autophagy inhibitor chloroquine (CQ) (Figure 7H,M and Figure S3B).…”
Section: Ferritinophagy Is Involved In Hdminduced Cell Deathsupporting
confidence: 85%
“…In this study, we found that OVA‐induced airway inflammation was significantly suppressed in PGRN‐deficient mice, consistent with a proinflammatory role but not with the anti‐inflammatory role of PGRN in allergic asthma. 22 , 23 , 24 Therefore, in our study, we used PGRN deficient mice to investigate the role and possible mechanisms for PGRN regulation of the development of allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…GRN -deficient HaCaT cells display reduced LC3-II levels, and inhibition of the Wnt/β-catenin signalling pathway through IWP-2 treatment elevates the levels of LC3-II affected by GRN -deficiency ( Tian et al, 2016 ). Under other inflammatory-based conditions like asthma, recombinant GRN delivered nasally ameliorates indicators of impaired autophagy such as lowering protein levels of LC3, BECN1, and the number of autophagosomes in mice ( Liu et al, 2021 ). Liu et al (2021) show and postulate that these autophagic indicators may be regulated by GRN via high mobility group box 1 (HMGB1), a protein that is upstream of the MAPK/ERK pathway and is suppressed by GRN, which negatively modulates autophagy ( Figure 2 ).…”
Section: The Roles Of Cln Genes and Proteins In Au...mentioning
confidence: 99%
“…Under other inflammatory-based conditions like asthma, recombinant GRN delivered nasally ameliorates indicators of impaired autophagy such as lowering protein levels of LC3, BECN1, and the number of autophagosomes in mice ( Liu et al, 2021 ). Liu et al (2021) show and postulate that these autophagic indicators may be regulated by GRN via high mobility group box 1 (HMGB1), a protein that is upstream of the MAPK/ERK pathway and is suppressed by GRN, which negatively modulates autophagy ( Figure 2 ). As GRN is known to be a protective biomolecule in the context of several neurodegenerative diseases, GRN may be asserting its protective effect against excitotoxicity within the autolysosomal pathway despite being an extracellular protein ( Davis et al, 2021 ; Terryn et al, 2021 ).…”
Section: The Roles Of Cln Genes and Proteins In Au...mentioning
confidence: 99%